2021
DOI: 10.1002/jssc.202001248
|View full text |Cite
|
Sign up to set email alerts
|

Isomer separation and analysis of amphiphilic polysialogangliosides using reversed‐phase liquid chromatography‐mass spectrometry

Abstract: Gangliosides are amphiphilic, acidic glycosphingolipids possessing one or more sialic acid residues and several isobaric structural isomers with different abundances and bioactivities. Therefore, the distinction between these isomers is crucial for their proper profiling. Although liquid chromatography-mass spectrometry has been successfully employed for this purpose, the distinction process can still be improved, particularly regarding liquid chromatography. Recently, a reversed-phase liquid chromatography me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…This suggested a potential relationship between the mobile phase pH and the chromatographic performance of PIPs, which is consistent with the literature on the chromatography of phosphorylated compounds [26]. Additionally, changes in retention time such as those observed in Figure 1 have previously been related to the pKb of the buffer anion [28]. However, as shown by the data in Table 1, peak widths and retention time produced by the buffers did not correlate with either buffer pH, or the anions pKb.…”
Section: Buffer Ph Pkb Rt (A) Rt (B) Rt (C) W (A) W (B) W (C)supporting
confidence: 89%
See 1 more Smart Citation
“…This suggested a potential relationship between the mobile phase pH and the chromatographic performance of PIPs, which is consistent with the literature on the chromatography of phosphorylated compounds [26]. Additionally, changes in retention time such as those observed in Figure 1 have previously been related to the pKb of the buffer anion [28]. However, as shown by the data in Table 1, peak widths and retention time produced by the buffers did not correlate with either buffer pH, or the anions pKb.…”
Section: Buffer Ph Pkb Rt (A) Rt (B) Rt (C) W (A) W (B) W (C)supporting
confidence: 89%
“…In addition to those advances previously made in the analysis of PIs, various sources throughout the literature have suggested a number of other variables which may be leveraged to pursue this goal. Experimental work regarding the influence of mobile phase pH and solvent composition has suggested that an alkaline and acetonitrile-based mobile phase may be sufficient to enhance the chromatographic retention, resolution, and ionization efficiency for these lipid classes [18,23,[26][27][28]. Furthermore, it is suggested that the chelation behavior and poor chromatographic performance of PIPs may be addressed through the use of certain specialized stationary phase technologies [29] and mobile phase additives [30], circumventing the previous necessity of ion-pairing agents and their potential for instrument contamination [27,31,32].…”
Section: Introductionmentioning
confidence: 99%